Topical Trabodenoson Is Neuroprotective in a Rodent Model of Anterior Ischemic Optic Neuropathy (rNAION) - Guo, Yan (Transl Vis Sci Technol, 2019)
PURPOSE: Nonarteritic anterior ischemic optic neuropathy (NAION) is the leading cause of sudden optic nerve–related vision loss currently without effective treatment. We evaluated the neuroprotective potential of ocular (topical) delivery of trabodenoson, a selective A(1) receptor mimetic, in a rodent model of NAION (rNAION). METHODS: Daily topical delivery of 3% trabodenoson or vehicle administered in both eyes 3 days prior to rNAION induction and for 21 days post induction. Retinal appearance and optic nerve head (ONH) edema was evaluated using spectral-domain optical coherence tomography (SD-OCT). Retinal function was evaluated before and after induction by ganzfeld electroretinography (ERG). Brn3a(+) retinal ganglion cells (RGCs) were quantified by stereology. Axonal ultrastructure was evaluated by electron microscopy. RESULTS: Trabodenoson-treated eyes had significantly reduced optic nerve (ON) edema compared with vehicle-treated eyes (ANOVA, P < 0.05). Electrophysiologically, there was a nonsignificant trend toward b-wave and oscillatory potential (OP) preservation in the trabodenoson-treated eyes. RGC counts were higher in trabodenoson-treated eyes compared to vehicle (74% versus 47% of the contralateral eye; two-tailed t-test; P = 0.01), as were ON axons. No overt morphologic differences in cell inflammation were observed between vehicle- and trabodenoson-treated ONHs, but trabodenoson-treated ONHs revealed increased expression of astrocyte-related neuroprotective responses. CONCLUSIONS: Trabodenoson preserves RGCs in the rodent NAION model. While previous clinical trials focused on trabodenoson's ocular antihypertensive effect, our data suggest trabodenoson's primary target may be both the retina and ONH. Selective adenosine A(1) agonists may prove an appropriate neuroprotective adjunctive for ischemia-related ON diseases such as NAION and glaucoma. TRANSLATIONAL RELEVANCE: RGC and ON neuroprotection in ischemic neuropathies may be achievable by topical administration of A(1) adenosine agonists rather than by simply relying on intraocular pressure reduction.